Human resource management in a global context : a critical approach - Kramar, Robin; Syed, Jawad (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2012)
"A global, contemporary and critical view of human resource management. Using international examples and case studies, this text covers the basic principles of HRM, whilst exposing students to real world issues facing managers on a daily basis. This text is essential reading for anyone who wants to understand and engage critically with HRM globally"--
Machine generated contents note: -- Introduction -- PART ONE: The Human Resource Management Arena -- 1.Contextualizing Human Resource Management -- 2. A Critical Perspective on Strategic Human Resource Management -- 3. Human Resource Management in Contemporary Transnational Companies -- 4. Diversity Management -- 5. Human Resource Management and Ethics -- PART TWO: Human Resource Management in Practice -- 6. Human Resource Planning -- 7. Job and Work Design -- 8. Recruitment and Selection -- 9. Performance Management -- 10. Reward Management -- 11. Training, Development and Learning -- PART THREE: Human Resource Management and Contemporary Issues -- 12. Change Management and Human Resource Management -- 13. Human Resource Management , Productivity and Employee Involvement -- Work Life Balance in the 21st Century -- Managing Human Resources and Quality -- Human Resource Management in Small to Medium Enterprises -- Conclusion -- Index.
Includes bibliographical references and index.
Keywords: BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / International / General; BUSINESS & ECONOMICS / Management; Personnel management